The Karakteristik Pasien Tonsilitis Kronis yang Menjalani Tonsilektomi di RSUD Abdoel Wahab Sjahranie Samarinda Tahun 2020-2022: Characteristics of Patients with Chronic Tonsillitis Undergoing Tonsillectomy at Abdoel Wahab Sjahranie Samarinda Regional General Hospital from 2020 to 2022 - Nabilah, Nur Alya; Pratiningrum, Moriko; Mu’ti, Abdul; Sawitri, Endang (Jurnal Medika : Karya Ilmiah Kesehatan, 2024)
Chronic tonsillitis is chronic inflammation of the tonsils following recurrent acute inflammation, with nonspecific causative microorganisms. The chronic inflammation results in tonsil enlargement due to parenchymal hyperplasia, causing OSAS (Obstructive Sleep Apnea Syndrome). Tonsillectomy is a surgical procedure that can be performed when chronic infection occurs. This study aimed to determine the characteristics of patients with chronic tonsillitis who underwent tonsillectomy at Abdoel Wahab Sjahranie Samarinda Hospital for the period 2020-2022. Descriptive observational research with a cross sectional approach using data on the target population, namely 85 medical records of chronic tonsillitis patients who underwent tonsillectomy at Abdoel Wahab Sjahranie Samarinda Hospital for the period 2020-2022. The results showed the age of toddlers (0-5 years) 10%, children (6-18 years) 55%, adults (19-45 years) 33%, elderly (>45 years) 2%; male gender 52%, and female 48%; tonsil size T2 37%, T3 55%, T4 8%; main complaints of snoring 51%, difficulty swallowing 8%, shortness of breath 6%, bad breath 2%, swallowing pain 92%, coughing 7%; leukopenia 5%, normal leukocytes 86%, leukocytosis 9%; normal ESR 58%, and ESR increased 42%. It is concluded that chronic tonsillitis patients who underwent tonsillectomy at Abdoel Wahab Sjahranie Samarinda Hospital for the period 2020-202 were mostly children, male gender, tonsil size T3, main complaints of swallowing pain, normal leukocytes, normal ESR.